FOREIGN TRANSIT TOURISM IN NORTH MACEDONIA: STATISTICAL ANALYSES AND DISCUSSION OF SALIENT ISSUES - Iliev, Dejan (Macedonian Geographical Society, 2019)
The paper examines the foreign transit tourism in N. Macedonia in the period 2009-2016. The paper aims to present the country’s accessibility to foreign transit tourists, to determine the characteristics of foreign transit tourists through appropriate indicators, to identify problems in transit tourism development, and to give some recommendations. Secondary data and different methods of obtaining results are used. The findings reveal that the share of foreign transit tourists in terms of foreign visitors on a one-day visit and foreign visitors on a temporary stay is significantly higher at the state level. Nevertheless, foreign transit tourists in the country is untapped potential; therefore, it is necessary to find concrete solutions to overcome the problems. Overall, the study offers a better understanding of the foreign transit tourism in N. Macedonia and provides some managerial recommendations for improving foreign transit tourism in the country.
Keywords: accessibility, foreign transit tourists, transit tourism, expenditure